Mekanisme Survival Selama Pandemi Covid-19: Belajar Dari Pengalaman Perempuan Single Mother di Perdesaaan Madura - Deviana Mayasari; Hoiril Sabariman (Sociology Department, Brawijaya University, 2021)
The impact of the Covid-19 pandemic adds to the burden for single mothers. In addition to performing two functions at once, pandemics force them to survive in difficult situations. This article describes the challenges facing single-mother as well as survival mechanisms during pandemics. Phenomenological studies are used, through direct observation and in-depth interviews conducted on single mother in Ponteh Village. Data showed some of the challenges single-mother faced during the pandemic. First, the increase in double load. One of the additional tasks a single mother does is the increasing burden of taking care of households due to school from home. Second, the decrease in income for household needs resulted from the government's mobility restriction policy. Third, the stereotype of women (widows) in a society that is bonded with social pressures. Survival mechanisms carried out by single mother during the pandemic include; First, fostering optimism and taking care of each other. Second, use social relationships. Third, downsize through reduced consumption and food substitutes, and fourth, diversify and intensify jobs. The scientific contribution of this article is, adding to the understanding that single mother women are no longer considered women who are unable to take care of the family. In fact, during helplessness and difficult challenges, they were able to overcome them